3‐Methylglutaconyl‐CoA hydratase deficiency: When ascertainment bias confounds a biochemical diagnosis. Issue 6 (14th September 2022) - Hertzog, Ashley; Selvanathan, Arthavan; Pandithan, Dinusha; Kim, Won‐Tae; Kava, Maina P.; Boneh, Avihu; Coman, David; Tolun, Adviye Ayper; Bhattacharya, Kaustuv
Abstract: 3‐Methylglutaconyl‐CoA hydratase deficiency (MGA1) is a defect in leucine catabolism, which causes the accumulation of urinary 3‐methylglutaconate, with or without 3‐hydroxyisovalerate and 3‐methylglutarate. It is an ultra‐rare condition, with <30 cases published in the literature. It is unclear whether the clinical features seen in reported patients are caused by the biochemical abnormalities, or whether they simply represent an ascertainment bias in patients that come to clinical attention. We reviewed the collective Australian experience of patients with confirmed MGA1, four of whom were diagnosed when asymptomatic through newborn screening (NBS). When our cohort is considered alongside the broader literature, there is no clear evidence of a specific childhood‐onset clinical phenotype associated with this disorder. Some patients have non‐specific clinical features (such as autism spectrum disorder [ASD]); however, there are also other family members with ASD in the absence of MGA1, suggesting a multifactorial aetiology. Importantly, all four patients diagnosed through NBS (including three with over 18 years of clinical follow‐up) remain asymptomatic in the absence of treatment. Based on the available literature, we suggest that MGA1 represents a biochemical phenotype, with an absence of a childhood clinical phenotype. The burdens of sustained treatment (particularly with intensive dietary leucine restriction) in asymptomatic individuals may be of little benefit, and likely to result in poor compliance. Longer‐term follow‐up of patients detected via NBS (or biochemical screening of large cohorts of asymptomatic adult individuals) will be required to conclusively prove or disprove the association with adult‐onset leukoencephalopathy.